Risk factors for functional decline in a population aged 75 years and older without total dependence: A one-year follow-up. (July 2016) - Arnau, Anna; Espaulella, Joan; Serrarols, Marta; Canudas, Judit; Formiga, Francesc; Ferrer, Montserrat
Highlights: Study of a representative sample of non-dependent >75 year-olds at primary care. The Short There are important gaps in the tools to deal with frailty in primary care. Physical Performance Battery is useful to identify elderly people at risk. Suitable management of hospitalization could protect the elderly's functional status. Abstract: Objectives: estimation of functional loss incidence and identification of risk factors associated with new disability onset in people aged 75 and older without severe dependence in a rural primary care setting. Patients and method: Prospective cohort study of a representative sample of people aged 75 years or older without severe dependence (Barthel Index > 20 and Lawton Index > 1) at a primary care center, with a 12-month follow-up. The baseline geriatric assessment recorded activities of daily living (ADL), sociodemographic information, numbers of drugs prescribed, previous hospital admissions and falls, cognitive function, hearing and visual capacity, body mass index, blood pressure, and the Short Physical Performance Battery to evaluate lower limb function. ADL was re-assessed after 12 months, defining functional loss as a fall of ≥10 points on the Barthel Index and/or ≥2 instrumental activities of the Lawton Index. Bivariate and multivariate analyses using logistic regression models were conducted to identify factors independently associated with functional loss. Results: Mean age was 81.7 years, 58.7% of patients were men, and 23.4% presented functional loss at the 12-month follow-up. Variables identified as independent predictors of functional loss were hospital admissions (aOR 3.92; 95%CI: 1.35–11.39), cognitive impairment (aOR 2.60; 95%CI: 1.39–4.92) and lower limbs functional limitation (aOR 2.01; 95%CI: 1.02–3.97). Conclusions: Our results support the use of performance batteries in primary care for identifying elderly persons at risk of functional decline; and they also highlight the relevance of appropriate management of hospital admissions and planned discharges in order to preserve patients' functional status.